Marginal adaptation in proximal cavities restored with composites and other materials - Raphaela Farias Rodrigues; Suellen Scarcelli Senna; Ana Flávia Soares; Rafael Lia Mondelli; Paulo Silveira Francisconi; Ana Flávia Sanches Borges (Brazilian Dental Science)
Objective: To evaluate the marginal adaptation, in enamel (E) and dentin (D), of composite resin (CR) associated with flowable resin composite (flow), bulk fill flowable base (bulk) and resin modified glass ionomer cement (RMGIC) in slot cavities. Material and Methods: The study was conducted after approval (Protocol No. 21148413.4.0000.5417) from Ethics Committee. Forty extracted human molar teeth were randomly assigned in eight experimental groups: E-CR, E-BULK, E-FLOW, E-RMGIC, D-CR, D-BULK, D-FLOW, D-RMGIC. The occlusal surface was planned, two slot cavities with standard sizes (depth: 2.0 mm, height: 2.5 mm, width: 2.0 mm) were created on a machine for making cavities. The teeth were restored and after 24h subjected to 2000 cyclic loading and sectioned for analysis of marginal adaptation by scanning electron microscopy (SEM). The micrographs were analyzed with the Image J program to measure the size of marginal gaps. The data were transformed into percentages (%GAPS = LG ÷ LM  × 100) and analyzed by 2-way ANOVA followed by the post hoc Tukey test (?=0.05). Results: There was a significant difference between different treatments (p<0.01). The groups E-RMGIC (p=0.001) and D-RMGIC (p=0) had the highest percentage of marginal gap. Others groups showed similar percentage of marginal gap (p>0.05). Conclusions: It was concluded that restorations with flowable composite resin and bulk fill liners exhibit the same behavior, but the RMGIC liner increased marginal gap.